The pathophysiology of sepsis and precision-medicine-based immunotherapy - Giamarellos-Bourboulis, Evangelos J.; Aschenbrenner, Anna C.; Bauer, Michael; Bock, Christoph; Calandra, Thierry; Gat-Viks, Irit; Kyriazopoulou, Evdoxia; Lupse, Mihaela; Monneret, Guillaume; Pickkers, Peter; Schultze, Joachim L.; van der Poll, Tom; et al. (Nature immunology, 2024)
Sepsis remains a major cause of morbidity and mortality in both low- and high-income countries. Antibiotic therapy and supportive care have significantly improved survival following sepsis in the twentieth century, but further progress has been challenging. Immunotherapy trials for sepsis, mainly aimed at suppressing the immune response, from the 1990s and 2000s, have largely failed, in part owing to unresolved patient heterogeneity in the underlying immune disbalance. The past decade has brought the promise to break this blockade through technological developments based on omics-based technologies and systems medicine that can provide a much larger data space to describe in greater detail the immune endotypes in sepsis. Patient stratification opens new avenues towards precision medicine approaches that aim to apply immunotherapies to sepsis, on the basis of precise biomarkers and molecular mechanisms defining specific immune endotypes. This approach has the potential to lead to the establishment of immunotherapy as a successful pillar in the treatment of sepsis for future generations. In this Review, Netea and colleagues summarize the latest research that contributes to our understanding of the pathophysiology of sepsis, and how this contributes to a new treatment approach through personalized immunotherapy.